PERPUSTAKAAN ANAK DI KOTA BANJARBARU - Maya, Tegar Indra; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Childhood is the most important period in teaching good habits to children for the growth of their mindset. One of the good habits that can be taught is reading books. Reading books from an early age can develop children's imagination so that it has a positive impact on their creative level for the present to the future. In response to this, of course, we need a special forum to facilitate reading activities especially for children. In Kota Banjarbaru itself, there is no special library for children, only a children's service from the Banjarbaru City Regional Library. The purpose of designing this children's library is as a learning support center as well as educational activities and recreational facilities for children with an age limit of 2-13 years through activities that teach skills and insights that are in accordance with the characteristics of the child, which can attract children's reading interest in the city of Banjarbaru. The main thing that is applied in the design of the children's library in the city of Banjarbaru is that the building has the flexibility for its users to easily and quickly adjust. The method used in designing children's libraries in the city of Banjarbaru uses a behavioral architecture approach as a consideration in designing to direct behavior and accommodate it and answer all problems that arise in the design process. Behavioral architecture is an architecture whose application includes behavioral considerations in the design. Because the main actors of the activity are dynamic children, the concept used is spatial flexibility.